The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1128/jb.00161-08
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Trimeric Autotransporter C-Terminal Domains of Oligomeric Coiled-Coil Adhesin (Oca) Family Members YadA, UspA1, EibA, and Hia to Translocation of the YadA Passenger Domain and Virulence ofYersinia enterocolitica

Abstract: The Oca family is a novel class of autotransporter-adhesins with highest structural similarity in their C-terminal transmembrane region, which supposedly builds a beta-barrel pore in the outer membrane (OM). The prototype of the Oca family is YadA, an adhesin of Yersinia enterocolitica and Yersinia pseudotuberculosis. Protein secretion in gram-negative bacteria is faced with the serious problem of traversing two different membrane-lipid bilayers. Therefore, several secretory pathways have evolved, which were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 55 publications
2
32
0
2
Order By: Relevance
“…The group of trimeric autotransporters is a large protein family consisting of virulence factors of diverse pathogenic gram-negative bacteria, such as the YadA protein of Yersinia spp. and the Hia protein of H. influenzae (1,33). Trimeric autotransporters mediate their own insertion into the outer membrane.…”
Section: Adhesion and Major Ompsmentioning
confidence: 99%
“…The group of trimeric autotransporters is a large protein family consisting of virulence factors of diverse pathogenic gram-negative bacteria, such as the YadA protein of Yersinia spp. and the Hia protein of H. influenzae (1,33). Trimeric autotransporters mediate their own insertion into the outer membrane.…”
Section: Adhesion and Major Ompsmentioning
confidence: 99%
“…Recent studies by Ackermann et al (1) have shown that only the factual membrane anchor domain of YadA is able to confer serum resistance and mouse virulence to Y. enterocolitica expressing chimeric fusion proteins of the N-terminal YadA passenger domain and the C-terminal membrane anchor domains of the TAAs UspA1 (Moraxella catarrhalis), EibA (Escherichia coli), and Hia (Haemophilus influenzae).…”
mentioning
confidence: 99%
“…Therefore we investigated the ability of full-length NadA produced on the surface of Y. enterocolitica to mediate interaction with immobilized collagen type I, fibronectin, and matrigel, respectively, using an ELISA technique (22). As expected NadA-positive yersiniae failed to bind any of the tested ECM proteins in contrast to YadA-positive yersiniae which are known to bind to different ECM proteins (11,23) (supplemental Fig.…”
Section: Nada-expressing Yersiniae Do Not Interact With Extracellularmentioning
confidence: 99%